2013
DOI: 10.1111/jph.12100
|View full text |Cite
|
Sign up to set email alerts
|

1‐Phenyl‐3‐pentanone, a Volatile Compound from the Edible Mushroom Mycoleptodonoides aitchisonii Active Against Some Phytopathogenic Fungi

Abstract: Volatiles produced by mycelia of mushrooms with aromatic odour were investigated for their antifungal activity against plant‐pathogenic fungi. The results of the screening of 23 species of basidiomycetes revealed that volatile substances from mycelia of Mycoleptodonoides aitchisonii (TUFC10099), an edible mushroom, strongly inhibited the mycelial growth, spore germination and lesion formation on host leaves of some plant‐pathogenic fungi including Alternaria alternata, A. brassicicola, A. brassicae, Colletotri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…sporotrichioides, causing postharvest disease in storage (Petrovi c et al 2013). In our previous study, 1-phenyl-3-pentanone (PP), a volatile compound from the edible mushroom M. aitchisonii, had antifungal activity (Nishino et al 2013). PP has fungistatic activity against a wide range of fungal pathogens, including A. alternata Japanese pear pathotype, A. brassicicola, Bi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…sporotrichioides, causing postharvest disease in storage (Petrovi c et al 2013). In our previous study, 1-phenyl-3-pentanone (PP), a volatile compound from the edible mushroom M. aitchisonii, had antifungal activity (Nishino et al 2013). PP has fungistatic activity against a wide range of fungal pathogens, including A. alternata Japanese pear pathotype, A. brassicicola, Bi.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that 1‐phenyl‐3‐pentanone, a volatile compound from the edible mushroom Mycoleptodonoides aitchisonii, has antifungal activity against some phytopathogenic fungi (Nishino et al. ; Oka et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have made an extract library of the mushrooms. Using this library, we initiated an investigation of the bioactive compounds present in these strains and have identified several antimicrobial compounds 3,4) and new tyrosinase inhibitors. 5) These findings strongly suggested that there remain many opportunities to discover new specialized metabolites with biological activity in mushrooms.…”
Section: Introductionmentioning
confidence: 99%
“…The Fungus/Mushroom Resource and Research Center (FMRC), Tottori University possesses a collection of mushroom strains (8387 strains belonging to 1400 species, as on March 2017), which is one of the largest mushroom collections in the world. Recently, the analyses of bioactive compounds present in these strains have been initiated, which have resulted in the identification of several antimicrobial compounds [16,17]. We performed a screening for the extracts derived from the fruiting bodies and liquid cultures of the FMRC-preserved edible mushroom strains, in an attempt to identify novel tyrosinase inhibitors.…”
mentioning
confidence: 99%